2023
DOI: 10.1021/acs.jafc.3c01899
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Fluorescent Maillard Reaction Intermediates of Peptide and Glucose during Thermal Reaction and Its Mechanism

Abstract: The dynamic changes in fluorescence intensity of the Maillard reactions of l-alanyl-l-glutamine (Ala-Gln)/Diglycine (Gly-Gly)/glycyl-l-glutamine (Gly-Gln) and glucose were investigated. It was found that the fluorescence intensity would increase with the reaction time; however, it would decrease after longer heating at higher temperatures, which was accompanied by rapid browning. The strongest intensity occurred at 45, 35, and 35 min at 130 °C for Ala-Gln, Gly-Gly, and Gly-Gln systems, respectively. The simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…The fluorescence intensity of MRIs generated at various reaction conditions is shown in Figure A–I. Each sample presented a broad fluorescence spectral peak in the range of 410–430 nm, which was consistent with the results of previous studies . As shown in Figure A–D, the fluorescence intensities of MRIs increased slowly with a prolonged reaction time at 50 and 55 °C, and no significant changes ( p < 0.05) in browning intensities were found, indicating that the Maillard reaction was limited at 50 and 55 °C.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The fluorescence intensity of MRIs generated at various reaction conditions is shown in Figure A–I. Each sample presented a broad fluorescence spectral peak in the range of 410–430 nm, which was consistent with the results of previous studies . As shown in Figure A–D, the fluorescence intensities of MRIs increased slowly with a prolonged reaction time at 50 and 55 °C, and no significant changes ( p < 0.05) in browning intensities were found, indicating that the Maillard reaction was limited at 50 and 55 °C.…”
Section: Resultssupporting
confidence: 88%
“…Each sample presented a broad fluorescence spectral peak in the range of 410−430 nm, which was consistent with the results of previous studies. 18 As shown in Figure 1A−D, the fluorescence intensities of MRIs increased slowly with a prolonged reaction time at 50 and 55 °C, and no significant changes (p < 0.05) in browning intensities were found, indicating that the Maillard reaction was limited at 50 and 55 °C. As the temperature adjusted to 60 °C, the fluorescence intensity of MRIs increased significantly with time, while the browning intensity still showed a slower increase trend (Figure 1E,F); according to Pearson's correlation, a strong positive correlation between fluorescence intensity and browning degree was observed (r = 0.966, p < 0.01).…”
Section: Formation Of the Fluorescent Compounds As Browning Precursor...mentioning
confidence: 86%
See 2 more Smart Citations
“…The yields of 3-DX and GO gradually increased with the extension of reaction time in the deep-colored systems, especially for the latter one (Figure ). Xia et al monitored the reaction of the dipeptide–glucose model and found that short chain α-DCs could react quickly with small peptides to form a large number of fluorescent compounds, which were further converted into browning pigments. However, the production rate of 3-DX and GO in light-colored systems decreased largely, and the content was much lower than that of deep-colored one (Figure ).…”
Section: Resultsmentioning
confidence: 99%